Hot-dip galvanized steel sheet
The hot-dip plated steel sheet with controlled Si number densities in patterned and non-patterned areas addresses the challenges of durability and corrosion resistance, enabling durable and corrosion-resistant display of designs without printing, maintaining luster and visibility.
Patent Information
- Application Number
- JP2021021939
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-02-15
- Publication Date
- 2024-12-18
- Estimated Expiration
- 2041-02-15
Smart Images

Figure 0007602123000003 
Figure 0007602123000004 
Figure 0007602123000005
Abstract
Description
[Technical field]
[0001] The present invention relates to a hot-dip galvanized steel sheet. [Background technology]
[0002] Hot-dip galvanized steel sheets have excellent corrosion resistance, and Zn-Al-Mg-based hot-dip galvanized steel sheets have particularly excellent corrosion resistance. Such hot-dip galvanized steel sheets are widely used in various manufacturing industries, such as in the fields of building materials, home appliances, and automobiles, and their usage has been increasing in recent years.
[0003] Incidentally, in order to produce characters, patterns, designs, etc. on the surface of the hot-dip plated layer of a hot-dip plated steel sheet, the hot-dip plated layer may be subjected to a process such as printing or painting, thereby producing characters, patterns, designs, etc. on the surface of the hot-dip plated layer.
[0004] However, when a process such as printing or painting is performed on the hot-dip plating layer, there is a problem that the cost and time required to apply characters, designs, etc. are increased. Furthermore, when characters, designs, etc. are displayed on the surface of the plating layer by printing or painting, not only is the metallic gloss appearance that is highly popular among consumers lost, but the durability is also poor due to problems such as deterioration of the coating film itself over time and deterioration of the adhesion of the coating film over time, and there is a risk that the characters, designs, etc. will disappear over time. Furthermore, when characters, designs, etc. are displayed on the surface of the plating layer by stamping ink, although the cost and time can be relatively reduced, there is a concern that the corrosion resistance of the hot-dip plating layer will be reduced by the ink.
[0005] As shown in the following patent documents, various technical developments have been made for Zn-Al-Mg-based hot-dip plated steel sheets, but no technology is known for improving the durability of characters, designs, etc., when they are formed on the surface of the plating layer.
[0006] Regarding Zn-Al-Mg hot-dip coated steel sheets, there are prior art techniques aimed at improving the matte coating appearance seen in Zn-Al-Mg hot-dip coated steel sheets.
[0007] For example, Patent Document 1 describes a Zn-Al-Mg hot-dip plated steel sheet having a matte appearance with fine texture and many smooth shiny parts, i.e., a Zn-Al-Mg hot-dip plated steel sheet having a good matte appearance with many white parts per unit area and a large ratio of the area of shiny parts. Patent Document 1 also describes that an undesirable matte state is a surface appearance in which amorphous white parts and circular shiny parts are mixed and scattered on the surface.
[0008] Patent Document 2 describes a Zn-Al-Mg-plated steel sheet in which a portion in a cross section of the plating layer in the thickness direction, in which no Al crystals exist between the interface between the plating layer and the base steel and the plating surface layer, occupies 10% to 50% of the width direction length of the cross section, thereby improving the plating appearance.
[0009] Furthermore, Patent Document 3 describes a hot-dip galvanized steel sheet having excellent formability, in which the surface of the plated steel sheet has a center line average roughness Ra of 0.5 to 1.5 μm, a PPI (the number of peaks having a size of 1.27 μm or more contained per inch (2.54 cm)) of 150 to 300, and a Pc (the number of peaks having a size of 0.5 μm or more contained per cm) of Pc≧PPI / 2.54+10.
[0010] Furthermore, Patent Document 4 describes a highly corrosion-resistant hot-dip galvanized steel sheet in which the gloss of the plating layer is increased overall and the uniformity of appearance is improved by refining the ternary eutectic structure of Al / MgZn2 / Zn.
[0011] However, no technology has been known to date that can improve the durability of a plating layer when characters or the like are formed on the surface of the plating layer while preventing a decrease in corrosion resistance. [Prior art documents] [Patent documents]
[0012] [Patent Document 1] Patent No. 5043234 [Patent Document 2] Patent No. 5141899 [Patent Document 3] Patent No. 3600804 [Patent Document 4] International Publication No. 2013 / 002358 Summary of the Invention [Problem to be solved by the invention]
[0013] The present invention has been made in consideration of the above circumstances, and an object of the present invention is to provide a hot-dip plated steel sheet capable of displaying letters, designs, etc. on the surface of the hot-dip plated layer, which has excellent durability and corrosion resistance. [Means for solving the problem]
[0014] The gist of the present invention is as follows. [1] A steel plate and a hot-dip plating layer formed on a surface of the steel plate, The hot-dip plating layer contains, in an average composition, 4 to 22 mass% Al, 1.0 to 10 mass% Mg, 0.01 to 2.0 mass% Si, and the remainder contains Zn and impurities, The hot-dip coating layer contains an intermetallic compound Mg2Si at the interface between the hot-dip coating layer and the steel sheet, The hot-dip plating layer has a pattern portion and a non-pattern portion arranged to have a predetermined shape, The number density of Mg2Si per area in the patterned portion is 2.0 times or more the number density of Mg2Si per area in the non-patterned portion. the law of nature, Mg per area in the pattern portion 2 The density of Si is 100 pieces / mm 2 That's all. The pattern portion is intentionally formed. The hot-dip galvanized steel sheet is characterized by the above. [2] The density of Mg2Si particles per area in the non-patterned portion is 1000 particles / mm 2 The hot-dip galvanized steel sheet according to [1], characterized in that: [3] The hot-dip plated steel sheet according to [1] or [2], characterized in that the hot-dip plated layer further contains, in an average composition, one or more of Ni, Ti, Zr, Sr, Fe, Sb, Pb, Sn, Ca, Co, Mn, P, B, Bi, Cr, Sc, Y, REM, Hf, and C in a total amount of 0.0001 to 2 mass%. [4] The hot-dip galvanized steel sheet according to any one of [1] to [3], characterized in that the pattern portion is arranged so as to have one or a combination of two or more of a straight line portion, a curved line portion, a dot portion, a figure, a number, a symbol, a design, or a letter. 。 [ 5 The coating weight of the hot-dip coating layer is 30 to 600 g / m2 in total on both sides of the steel sheet. 2 [1] to [ 4 ] The hot-dip plated steel sheet according to any one of claims 1 to 5. Effect of the Invention
[0015] According to the present invention, it is possible to provide a hot-dip plated steel sheet which is capable of producing characters, designs, etc. on the surface of the hot-dip plated layer and which is excellent in durability and corrosion resistance. [Brief description of the drawings]
[0016] [Figure 1] This is a scanning electron microscope photograph of the pattern part of No.1. [Diagram 2] 1 is a scanning electron microscope photograph of the non-patterned portion of No. 1. [Diagram 3] 1 is a photograph showing an example of the surface of a hot-dip plated layer of a hot-dip plated steel sheet according to the present embodiment, showing a state in which a predetermined pattern is revealed by a pattern portion. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] A hot-dip galvanized steel sheet according to an embodiment of the present invention will be described. The hot-dip plated steel sheet of the present embodiment comprises a steel sheet and a hot-dip plated layer formed on the surface of the steel sheet, the hot-dip plated layer containing, in average composition, 4-22 mass% Al, 1.0-10 mass% Mg, 0.01-2.0 mass% Si, with the balance containing Zn and impurities, the hot-dip plated layer containing Mg2Si which is an intermetallic compound at the interface with the hot-dip plated layer, and further, the hot-dip plated layer is formed with a pattern portion and a non-pattern portion arranged to have a predetermined shape, and the number density per area of Mg2Si in the pattern portion is 2.0 times or more the number density per area of Mg2Si in the non-pattern portion.
[0018] In the hot-dip galvanized steel sheet of this embodiment, the number density of Mg2Si present at the interface between the hot-dip galvanized layer and the steel sheet is locally changed to form patterned and non-patterned parts on the plated surface. In the patterned part, the number density of Mg2Si per area is relatively high, resulting in a glossy appearance. On the other hand, in the non-patterned part, the number density of Mg2Si per area is lower than that of the patterned part, resulting in a matte appearance in which fine glossy areas and fine white areas are mixed.
[0019] In this embodiment, the interface between the hot-dip galvanized layer and the steel sheet is the grinding surface having the highest number density of Mg2Si among a plurality of grinding surfaces exposed by stepwise grinding the hot-dip galvanized layer from the surface. In this embodiment, the grinding surface closest to the steel sheet among the grinding surfaces successively exposed to the hot-dip galvanized layer often becomes the interface between the hot-dip galvanized layer and the steel sheet.
[0020] In this way, depending on the difference in the number density per area of Mg2Si in the hot-dip plating layer, the surface of the hot-dip plating layer appears either glossy or matte depending on the location. Here, in order to make characters, figures, lines, dots, patterns, etc. visible on the surface of the hot-dip plating layer, it is sufficient to be able to distinguish the patterned parts constituting these characters, etc. from the other non-patterned parts. To this end, it is preferable that the number density per area of Mg2Si in the patterned parts is 2.0 times or more the number density per area of Mg2Si in the non-patterned parts. This makes it possible to distinguish the patterned parts from the non-patterned parts.
[0021] In order to manufacture the hot-dip plated steel sheet of this embodiment, in the so-called hot-dip plating method in which the steel sheet is immersed in a hot-dip plating bath and then pulled up, liquid nitrogen is sprayed on the molten metal immediately after pulling up. The liquid nitrogen is sprayed locally on the molten metal on the opposite side, not on the side on which the pattern part is formed. The area to which the liquid nitrogen is sprayed corresponds to the area where the pattern part is formed. By locally spraying the liquid nitrogen on the molten metal on the opposite side to the side on which the pattern part is formed, the molten metal on the side on which the pattern part is formed is cooled from the steel sheet side. In the area locally cooled from the steel sheet side, many fine Mg2Si are formed at the interface between the hot-dip plating layer and the steel sheet, compared to other areas, and the number density of Mg2Si is high. In the area where the number density of Mg2Si is relatively high, the [Al / Zn / MgZn2 ternary eutectic structure] in the hot-dip plating layer becomes finer as the solidification of the molten metal progresses, and this increases the gloss of the surface of the hot-dip plating layer. In this way, the pattern part is formed.
[0022] On the other hand, in areas where liquid nitrogen was not sprayed and cooling from the steel sheet side was not performed, coarse Mg2Si particles were formed, the number density of Mg2Si particles became relatively small, and the refinement of the [Al / Zn / MgZn2 ternary eutectic structure] in the hot-dip coating layer did not progress, resulting in a matte appearance on the surface of the hot-dip coating layer. Such areas become non-patterned areas.
[0023] In this way, by partially spraying liquid nitrogen onto the molten metal adhering to the surface of the steel sheet opposite to the surface on which the pattern portion is formed after the steel sheet is pulled out of the hot-dip galvanizing bath, it becomes possible to control the number density of Mg2Si at the interface between the steel sheet and the hot-dip galvanized layer, and thereby it becomes possible to intentionally form a pattern portion having a predetermined shape that has a relatively high gloss and is distinguishable from a non-pattern portion.
[0024] The hot-dip galvanized steel sheet of the present embodiment will be described in detail below.
[0025] There is no particular restriction on the material of the steel sheet that serves as the base of the hot-dip coating layer. As will be described in detail later, general steel and the like can be used as the material without any particular restriction, and Al-killed steel and some high alloy steels can also be applied, and there is no particular restriction on the shape. The hot-dip coating layer according to this embodiment is formed by applying the hot-dip coating method described later to the steel sheet.
[0026] Next, the chemical components of the hot-dip plating layer will be described. The hot-dip coating layer contains, in an average composition, Al: 4-22 mass%, Mg: 1.0-10 mass%, Si: 0.01-2.0 mass%, and the balance is Zn and impurities. More preferably, the average composition contains Al: 4-22 mass%, Mg: 1.0-10 mass%, Si: 0.01-2.0 mass%, and the balance is Zn and impurities. The hot-dip coating layer may contain, in an average composition, 0.0001-2 mass% in total of one or more of Ni, Ti, Zr, Sr, Fe, Sb, Pb, Sn, Ca, Co, Mn, P, B, Bi, Cr, Sc, Y, REM, Hf, and C.
[0027] The Al content is in the range of 4 to 22 mass% in the average composition. Al is preferably contained to ensure corrosion resistance. If the Al content in the hot-dip plating layer is 4 mass% or more, the effect of improving corrosion resistance is further enhanced. If it exceeds 22 mass%, the effect of improving corrosion resistance is saturated. From the viewpoint of corrosion resistance, it is preferably 5 to 18 mass%, and more preferably 6 to 16 mass%.
[0028] The content of Mg is in the range of 1.0 to 10 mass% in the average composition. Mg is preferably added to improve corrosion resistance. If the content of Mg in the hot-dip coating layer is 1.0 mass% or more, the effect of improving corrosion resistance is further enhanced. However, if the content of Mg exceeds 10 mass%, dross generation in the coating bath becomes significant, making it difficult to stably manufacture hot-dip coated steel sheets, so the content of Mg is set to 10 mass% or less. From the viewpoint of the balance between corrosion resistance and dross generation, the content of Mg is preferably set to 1.5 to 6.0 mass%, and more preferably set to the range of 2.0 to 5.0 mass%.
[0029] The content of Si is in the range of 0.01 to 2.0 mass% in the average composition. Si is contained to form Mg2Si, which is necessary for providing a patterned portion and a non-patterned portion. If the content of Si in the hot-dip plating layer is 0.01 mass% or more, the effect of forming a patterned portion and a non-patterned portion can be obtained. On the other hand, even if Si is contained so as to exceed 2.0 mass%, the effect of forming a patterned portion and a non-patterned portion is saturated, so that the content of Si is set to 2.0 mass% or less. From the viewpoint of plating adhesion, the content of Si is preferably set to the range of 0.02 to 1.0 mass%, more preferably set to the range of 0.05 to 0.8 mass%, and even more preferably set to the range of 0.1 to 0.8 mass%.
[0030] The hot-dip plating layer may contain, in average composition, one or more of Ni, Ti, Zr, Sr, Fe, Sb, Pb, Sn, Ca, Co, Mn, P, B, Bi, Cr, Sc, Y, REM, Hf, and C in a total amount of 0.0001 to 2 mass%. By containing these elements, the corrosion resistance of the hot-dip plating layer can be further improved. REM is one or more of rare earth elements having atomic numbers 57 to 71 in the periodic table.
[0031] The balance of the chemical composition of the hot-dip coating is zinc and impurities. Some of the impurities are inevitably contained in zinc and other ingots, while others are contained in the coating bath as the steel dissolves.
[0032] The average composition of the hot-dip plating layer can be measured by the following method. First, the surface coating is removed with a coating remover that does not corrode the coating (e.g., Neo River SP-751 manufactured by Sansai Kako Co., Ltd.), then the hot-dip plating layer is dissolved with hydrochloric acid containing an inhibitor (e.g., Hibilon manufactured by Sugimura Chemical Industry Co., Ltd.), and the resulting solution is subjected to inductively coupled plasma (ICP) emission spectrometry. In addition, if there is no surface coating, the work of removing the surface coating can be omitted.
[0033] Next, the structure of the hot-dip plated layer will be described.
[0034] The hot-dip coating layer containing Al, Mg, and Zn contains an [Al phase] and an [Al / Zn / MgZn2 ternary eutectic structure]. The [Al phase] is contained in the matrix of the [Al / Zn / MgZn2 ternary eutectic structure]. In addition, since the hot-dip coating layer of this embodiment contains Si, the matrix of the [Al / Zn / MgZn2 ternary eutectic structure] contains Mg2Si, which is an intermetallic compound. Furthermore, the matrix of the [Al / Zn / MgZn2 ternary eutectic structure] may contain an [MgZn2 phase] or a [Zn phase].
[0035] [Al / Zn / MgZn2 ternary eutectic structure] is a ternary eutectic structure of an Al phase, a Zn phase, and an intermetallic compound MgZn2 phase. The Al phase forming this ternary eutectic structure corresponds to, for example, the "Al" phase (an Al solid solution that dissolves Zn and contains a small amount of Mg) at high temperatures in an Al-Zn-Mg ternary equilibrium phase diagram. This Al" phase at high temperatures usually appears separated into a fine Al phase and a fine Zn phase at room temperature. The Zn phase in the [Al / Zn / MgZn2 ternary eutectic structure] is a Zn solid solution with a small amount of Al in solid solution and, in some cases, an even smaller amount of Mg in solid solution. The MgZn2 phase in the [Al / Zn / MgZn2 ternary eutectic structure] is an intermetallic compound phase that exists in the vicinity of approximately 84 mass% Zn in the Zn-Mg binary equilibrium phase diagram. As can be seen from the phase diagram, it is thought that other added elements are not solid-dissolved in each phase, or even if they are solid-dissolved, the amount is extremely small, but the amounts cannot be clearly distinguished by normal analysis, so in this specification, the ternary eutectic structure consisting of these three phases is referred to as [Al / Zn / MgZn2 ternary eutectic structure].
[0036] The [Al phase] is a phase that appears as islands with clear boundaries in the matrix of the [Al / Zn / MgZn2 ternary eutectic structure], and corresponds to, for example, the "Al" phase (an Al solid solution with Zn, containing a small amount of Mg) at high temperatures in the Al-Zn-Mg ternary equilibrium phase diagram. The amounts of Zn and Mg dissolved in this Al" phase at high temperatures differ depending on the Al and Mg concentrations in the plating bath. This Al" phase at high temperatures normally separates into a fine Al phase and a fine Zn phase at room temperature, but the island-like shape seen at room temperature can be considered to be a remnant of the Al" phase at high temperatures. As can be seen from the phase diagram, this phase is thought to have no other added elements dissolved in it, or even if they are dissolved, the amount is extremely small, but since this cannot be clearly distinguished by normal analysis, the phase that originates from the Al" phase at high temperatures and retains the morphology of the Al" phase is referred to as the [Al phase] in this specification. This [Al phase] can be clearly distinguished from the Al phase that forms the above-mentioned [Al / Zn / MgZn2 ternary eutectic structure] when observed with a microscope.
[0037] The Zn phase is an island-like phase with clear boundaries in the base material of the Al / Zn / MgZn2 ternary eutectic structure, and may actually contain a small amount of Al and even a small amount of Mg in solid solution. As seen from the phase diagram, this phase does not contain any other additive elements in solid solution, or even if it does, it is in a very small amount. This Zn phase can be clearly distinguished from the Zn phase forming the Al / Zn / MgZn2 ternary eutectic structure by microscopic observation. The plating layer of the present invention may contain a Zn phase depending on the manufacturing conditions, but since there was almost no effect on improving the corrosion resistance of the processed part in the experiment, there is no particular problem even if the plating layer contains a Zn phase.
[0038] In addition, the [MgZn2 phase] is a phase that appears as islands with clear boundaries in the base material of the [Al / Zn / MgZn2 ternary eutectic structure], and may actually contain a small amount of Al in solid solution. As seen from the phase diagram, it is considered that other additive elements are not solid-dissolved in this phase, or even if they are solid-dissolved, the amount is extremely small. This [MgZn2 phase] can be clearly distinguished from the MgZn2 phase that forms the [Al / Zn / MgZn2 ternary eutectic structure] in microscopic observation. The hot-dip coating layer of this embodiment may not contain the [MgZn2 phase] depending on the manufacturing conditions, but it is contained in the hot-dip coating layer under most manufacturing conditions.
[0039] Mg2Si is a phase that appears as islands with clear boundaries in the solidification structure of the hot-dip coating layer. In the patterned area, the presence of many fine Mg2Si particles increases the number density of Mg2Si, which refines the [Al / Zn / MgZn2 ternary eutectic structure]. On the other hand, in the non-patterned area, Mg2Si grows coarsely, which reduces the number density of Mg2Si, which prevents the [Al / Zn / MgZn2 ternary eutectic structure] from being refined. As seen from the phase diagram, it appears that Zn, Al, and other added elements are not in solid solution, or even if they are, the amount is extremely small. This Mg2Si can be clearly distinguished when observed under a microscope in the coating.
[0040] Next, the patterned portion and the non-patterned portion on the surface of the hot-dip plated layer will be described.
[0041] The surface of the hot-dip plated layer of this embodiment has a patterned portion and a non-patterned portion arranged to have a predetermined shape. The patterned portion is preferably arranged to have a shape of one of straight line portions, curved portions, dot portions, figures, numbers, symbols, patterns, or letters, or a combination of two or more of these. The non-patterned portion is an area other than the patterned portion. The shape of the patterned portion is acceptable even if it is partially missing, such as a missing dot, as long as it can be recognized as a whole. The non-patterned portion may have a shape that borders the boundary of the patterned portion.
[0042] When the surface of the hot-dip plated layer has one or a combination of two or more of straight lines, curved lines, dots, figures, numbers, symbols, patterns, or letters, these areas can be patterned, and the other areas can be non-patterned. The boundary between the patterned and non-patterned parts can be seen with the naked eye. The boundary between the patterned and non-patterned parts can also be seen from a magnified image using an optical microscope or a magnifying glass.
[0043] The patterned portion is preferably formed to a size that allows the presence of the patterned portion to be discerned with the naked eye, under a magnifying glass, or under a microscope. The non-patterned portion is a region that occupies most of the hot-dip galvanized layer (the surface of the hot-dip galvanized layer), and the patterned portion may be arranged in the non-patterned portion. The patterned portion is arranged in a predetermined shape in the non-patterned portion. Specifically, the patterned portion is arranged in the non-patterned portion so as to have a shape that is one of straight lines, curved lines, figures, dots, figures, numbers, symbols, patterns, or letters, or a combination of two or more of these. By intentionally adjusting the shape of the patterned portion, a shape that is one of straight lines, curved lines, figures, dots, figures, numbers, symbols, patterns, or letters, or a combination of two or more of these, is formed on the surface of the hot-dip galvanized layer. For example, a character string, a number string, a symbol, a mark, a line diagram, a design, or a combination of these, which is made up of the patterned portion, is formed on the surface of the hot-dip galvanized layer. This shape is a shape that is intentionally or artificially formed by a manufacturing method described later, and is not formed naturally.
[0044] The patterned portion and the non-patterned portion contain [Al phase] and [Al / Zn / MgZn2 ternary eutectic structure]. The patterned portion and the non-patterned portion may contain [MgZn2 phase] and [Zn phase] in the matrix of [Al / Zn / MgZn2 ternary eutectic structure]. Furthermore, at least the patterned portion contains Mg2Si. The non-patterned portion may contain Mg2Si. The number density of Mg2Si per area in the patterned portion is 2.0 times or more the number density of Mg2Si per area in the non-patterned portion. The number density of Mg2Si per area in the non-patterned portion is 1000 pieces / mm 2 It is preferable that:
[0045] It is believed that Mg2Si formed in the hot-dip coating layer has the effect of becoming the starting point for the solidification of the [Al / Zn / MgZn2 ternary eutectic structure], and by increasing the number density of Mg2Si, the number of [Al / Zn / MgZn2 ternary eutectic structures] formed increases, resulting in the refinement of the [Al / Zn / MgZn2 ternary eutectic structure]. When the [Al / Zn / MgZn2 ternary eutectic structure] is refined, the fine [Al / Zn / MgZn2 ternary eutectic structure] solidifies so that the arborescence of the dendrites of the initial phase [Al phase] is completely filled, so that the exposed dendrites of the Al phase are reduced, and the [Al / Zn / MgZn2 ternary eutectic structure] with metallic luster covers the surface of the hot-dip coating layer.
[0046] Since the number density of Mg2Si per area is higher in the patterned portion than in the non-patterned portion, the patterned portion has a high gloss appearance. On the other hand, since the number density of Mg2Si per area is lower in the non-patterned portion than in the patterned portion, the non-patterned portion does not have the same gloss as the patterned portion, and has a matte appearance in which fine glossy areas and fine white areas are mixed. When the number density of Mg2Si per area in the patterned portion is 2.0 times or more the number density of Mg2Si per area in the non-patterned portion, it becomes possible to distinguish the patterned portion from the non-patterned portion. When the number density of Mg2Si in the patterned portion is less than 2.0 times the number density of Mg2Si in the non-patterned portion, the appearances of the patterned portion and the non-patterned portion become similar, making it difficult to distinguish the patterned portion. The greater the difference in number density, the better, and it is more preferable that it is 2.2 times or more, and even more preferable that it is 2.5 times or more.
[0047] In addition, the density of Mg2Si particles per area in the non-patterned area is 1000 particles / mm 2 When the gloss level of the non-patterned portion is below 500 pcs / mm, the difference in gloss level between the non-patterned portion and the patterned portion increases, making it possible to more clearly distinguish the patterned portion. 2 It may be less than 100 pieces / mm2 It may be less than 50 pieces / mm 2 It may be the following.
[0048] The density of Mg2Si particles in the pattern portion is not particularly limited, but may be, for example, 1000 particles / mm 2 It may be more than 1200 pieces / mm 2 More than 1300 pieces / mm 2 The number density of Mg2Si in the pattern portion may be approximately constant within the pattern portion, or may be a mixture of regions with high and low number densities within the pattern portion.
[0049] The patterned portion and the non-patterned portion may be distinguishable with the naked eye, or may be distinguishable under a magnifying glass or a microscope. Distinguishing under a magnifying glass or a microscope means, for example, that the shape constituted by the patterned portion is distinguishable in a visual field of 50 times or less. In a visual field of 50 times or less, the patterned portion and the non-patterned portion are distinguishable due to the difference in their appearance. The patterned portion and the non-patterned portion are distinguishable preferably at 20 times or less, more preferably at 10 times or less, and more preferably at 5 times or less.
[0050] The method for measuring the number density of Mg2Si is as follows. The hot-dip galvanized layer is gradually ground from the surface, the newly revealed ground surface is observed under an electron microscope, and the number density of Mg2Si on the ground surface is measured. This operation is repeated until the steel sheet surface is exposed. The amount of grinding per time is, for example, 1 μm deep. The number density of Mg2Si on each ground surface is compared, and the ground surface with the highest number density of Mg2Si is taken as the interface between the hot-dip galvanized layer and the steel sheet. The number density of Mg2Si on the interface is taken as the number density of Mg2Si in the patterned or non-patterned part. The number density is measured for each patterned and non-patterned part. The observation area for measuring the number density is 0.2 mm2. 2 The above range is preferable.
[0051] Moreover, the Mg2Si to be measured is Mg2Si with a circle equivalent diameter of 0.2 μm or more. To measure the circle equivalent diameter of Mg2Si, the target Mg2Si is image-processed in the SEM photograph taken as described above to obtain the projected area and calculate the circle equivalent diameter. When Mg2Si of the same crystal is observed to be divided by other phases, the area of the other dividing phases can also be considered to be the Mg2Si, and the circle equivalent diameter can be obtained.
[0052] The hot-dip galvanized steel sheet according to the present embodiment may have a chemical conversion coating layer or a coating layer on the surface of the hot-dip galvanized layer. Here, the type of the chemical conversion coating layer or the coating layer is not particularly limited, and a known chemical conversion coating layer or coating layer can be used.
[0053] [Manufacturing method of Zn-Al-Mg-based hot-dip plated steel sheet] Next, a method for producing the hot-dip plated steel sheet according to this embodiment will be described. The hot-dip plated steel sheet of the present embodiment is produced by hot-dip plating a steel sheet produced through steelmaking, casting, and hot rolling. After the hot rolling, pickling, hot-rolled sheet annealing, cold rolling, and cold-rolled sheet annealing may be further performed, and then hot-dip plating may be performed. The hot-dip plating is a continuous hot-dip plating method in which the steel sheet is continuously passed through a hot-dip plating bath.
[0054] The hot-dip galvanizing bath preferably contains Al: 4-22 mass%, Mg: 1.0-10 mass%, Si: 0.01-2.0 mass%, and the balance is Zn and impurities. The hot-dip galvanizing bath may contain Al: 4-22 mass%, Mg: 1.0-10 mass%, Si: 0.01-2.0 mass%, and the balance is Zn and impurities. The hot-dip galvanizing bath may further contain one or more of Ni, Ti, Zr, Sr, Fe, Sb, Pb, Sn, Ca, Co, Mn, P, B, Bi, Cr, Sc, Y, REM, Hf, and C in a total amount of 0.0001-2 mass%. The average composition of the hot-dip galvanizing layer in this embodiment is almost the same as the composition of the hot-dip galvanizing bath.
[0055] The temperature of the hot-dip galvanizing bath differs depending on the composition, but is preferably in the range of, for example, 400 to 500° C. This is because if the temperature of the hot-dip galvanizing bath is in this range, a desired hot-dip galvanized layer can be formed. The coating weight of the hot-dip coating layer may be adjusted by gas wiping or other means on the steel sheet pulled out of the hot-dip coating bath. The coating weight of the hot-dip coating layer is 30 to 600 g / m2 in total on both sides of the steel sheet. 2 It is preferable to adjust the amount of adhesion so that it is in the range of 30 g / m 2 If the coating weight is less than 600g / m, the corrosion resistance of the hot-dip galvanized steel sheet decreases, which is not preferable. 2 If the thickness exceeds 100 mm, the molten metal adhering to the steel sheet will drip, making it impossible to smooth the surface of the hot-dip plated layer, which is not preferable.
[0056] In this embodiment, liquid nitrogen is locally sprayed by a nozzle onto the molten metal adhering to the surface of the steel sheet opposite to the surface on which the pattern portion is to be formed, immediately after the steel sheet is pulled out of the hot-dip galvanizing bath. The optimum temperature range for the molten metal when spraying the liquid nitrogen varies depending on the composition. For example, in a plating composition of Al: 11%, Mg: 3%, and Si: 0.2%, liquid nitrogen is sprayed when the temperature of the molten metal is in the range of 380°C to 390°C. The area onto which the liquid nitrogen is sprayed corresponds to the area on which the pattern portion is to be formed.
[0057] The optimum temperature of the molten metal when spraying liquid nitrogen is preferably determined by experiment, but it is also possible to estimate the optimum temperature range by using, for example, the thermodynamic equilibrium calculation software "Thermo-Calc" (Thermo-Calc is a registered trademark, manufactured by Thermo-Calc Software Inc.), and the optimum temperature can be determined based on the results of this estimation. In the thermodynamic equilibrium calculation using "Thermo-Calc" (registered trademark), a general database is used, and as a phase to be excluded from the calculation, Mg2Zn, which is difficult to observe in the actual plating structure, is excluded. 11After specifying the Al phase and the Si phase, the formation start temperature of Mg2Si in the target composition is calculated. Since the actual formation temperature of Mg2Si is about 10 to 40°C lower than the above calculated temperature due to the influence of supercooling and the amount of formation, the temperature range is estimated as the optimal temperature range of the molten metal when spraying liquid nitrogen. For example, the formation start temperature of Mg2Si calculated in a plating composition of Al: 11%, Mg: 3%, and Si: 0.2% is about 400°C, so liquid nitrogen is sprayed when the temperature of the molten metal is in the range of 360°C to 390°C, preferably in the range of 380°C to 390°C. Note that the thermodynamic equilibrium calculation software used for the calculation is not limited to "Thermo-Calc" (registered trademark), and other software may be used.
[0058] If the temperature of the molten metal when the liquid nitrogen is sprayed is too low, the Mg2Si may not be finely divided, and a clear pattern may not be formed. Also, if the temperature of the molten metal when the liquid nitrogen is sprayed is too high, the cooling by the liquid nitrogen may be insufficient, the Mg2Si may not be finely divided, and a clear pattern may not be formed.
[0059] In the area where liquid nitrogen is sprayed, the cooling rate of the molten metal increases, and as a result, many fine Mg2Si are formed at the interface between the hot-dip layer and the steel sheet on the side opposite to the side where liquid nitrogen is sprayed, i.e., the side where the pattern portion is to be formed. On the other hand, in the area where liquid nitrogen is not sprayed, the Mg2Si becomes coarse and the number of Mg2Si particles decreases. In the area where fine and many Mg2Si particles are formed, the [Al / Zn / MgZn2 ternary eutectic structure] is refined, and the surface of the hot-dip layer becomes glossy. On the other hand, in the area where coarse and few Mg2Si particles are formed, the [Al / Zn / MgZn2 ternary eutectic structure] is not refined, and the surface of the hot-dip layer becomes matte. In this way, the area where liquid nitrogen is sprayed and the area where it is not sprayed in the hot-dip layer have different appearances from each other.
[0060] As described above, by adjusting the amount and range of liquid nitrogen sprayed, the shape of the patterned portion can be adjusted as desired, and the patterned portion and non-patterned portion can be distinguished with the naked eye.
[0061] Liquid nitrogen should be sprayed not on the molten metal attached to the surface on which the pattern is formed, but on the molten metal attached to the opposite surface. This is because when liquid nitrogen is sprayed directly onto the molten metal, the surface of the hot-dip plating layer becomes wavy when the liquid nitrogen expands due to evaporation, and the desired glossy appearance is not achieved, resulting in an appearance closer to a matte finish. If liquid nitrogen is sprayed from the opposite side to the surface on which the pattern is formed, the solidification of the molten metal on the side on which the pattern is formed begins from the side closer to the steel sheet, and by the time the temperature of the molten metal reaches the precipitation temperature of the [Al / Zn / MgZn2 ternary eutectic structure], a lot of Mg2Si precipitates, and these Mg2Si become the starting points of the [Al / Zn / MgZn2 ternary eutectic structure], which refines the [Al / Zn / MgZn2 ternary eutectic structure].
[0062] The liquid nitrogen is preferably sprayed onto the molten metal in a liquid state so that it adheres to the molten metal, in order to enhance the cooling efficiency. If the liquid nitrogen evaporates before adhering to the molten metal, the cooling efficiency decreases, and the refinement of Mg2Si does not progress.
[0063] The amount of liquid nitrogen sprayed is not particularly limited, but the optimal amount may vary depending on the composition of the hot-dip plated layer, the adhesion amount of the hot-dip plated layer, and the thickness of the steel sheet. Therefore, the optimal amount of liquid nitrogen sprayed can be adjusted by checking the pattern portion through preliminary tests or the like.
[0064] The pattern portion is not limited to being formed on only one of the hot-dip layers of the hot-dip plated steel sheet, but by adjusting the areas where the liquid nitrogen is sprayed so that they do not overlap, it is also possible to form the pattern portion on both sides of the hot-dip plated steel sheet.
[0065] Furthermore, in the case where a chemical conversion treatment layer is formed on the surface of the hot-dip plated layer, the hot-dip plated steel sheet after the hot-dip plated layer is formed is subjected to a chemical conversion treatment. The type of the chemical conversion treatment is not particularly limited, and a known chemical conversion treatment can be used. In addition, when a coating layer is formed on the surface of the hot-dip plated layer or the surface of the chemical conversion coating layer, a painting treatment is performed on the hot-dip plated steel sheet after the hot-dip plated layer or the chemical conversion coating layer is formed. The type of painting treatment is not particularly limited, and known painting treatments can be used.
[0066] In the hot-dip galvanized steel sheet of this embodiment, the number density of Mg2Si per area in the patterned portion is set to 2.0 times or more the number density of Mg2Si per area in the non-patterned portion, so that the patterned portion and the non-patterned portion can be distinguished from each other. The formed patterned portion and the non-patterned portion are not formed by printing or painting, and therefore have high durability. In addition, since the patterned portion and the non-patterned portion are not formed by printing or painting, there is no influence on the corrosion resistance of the hot-dip galvanized layer. Therefore, the hot-dip galvanized steel sheet of this embodiment has excellent corrosion resistance.
[0067] According to this embodiment, a hot-dip galvanized steel sheet having high durability in a pattern portion formed into a predetermined shape and suitable plating properties such as corrosion resistance can be provided. In particular, in this embodiment, by locally spraying liquid nitrogen, the range of the pattern portion or non-pattern portion can be intentionally or artificially shaped, and the pattern portion can be arranged so as to have a shape of one or a combination of two or more of straight lines, curved lines, dots, figures, numbers, symbols, patterns, or letters. This allows various designs, trademarks, and other identification marks to be displayed on the surface of the hot-dip galvanized layer without printing or painting, thereby improving the identification and designability of the source of the steel sheet. In addition, the pattern portion can also impart information necessary for process management, inventory management, and any information required by consumers to the hot-dip galvanized steel sheet. This can also contribute to improving the productivity of the hot-dip galvanized steel sheet. EXAMPLES
[0068] Next, an embodiment of the present invention will be described. After degreasing and washing the steel sheet, reduction annealing, immersion in a plating bath, coating weight control, and cooling were performed to produce Zn-Al-Mg-based hot-dip plated steel sheets No. 1 to 36 shown in Table 1A. Although it depends on the plating composition, in the case of a plating composition of Al: 11%, Mg: 3%, and Si: 0.2%, when the steel sheet was pulled up from the plating bath, liquid nitrogen was sprayed from a nozzle onto the molten metal on the steel sheet surface when the temperature of the molten metal was in the range of 380°C to 390°C. The molten metal was then completely solidified by cooling. The liquid nitrogen spray range was controlled to form a square pattern with one side of 50 mm. The area of the square pattern was defined as the patterned portion, and the area other than the square pattern was defined as the non-patterned portion. However, for No. 30, nitrogen gas was sprayed from a gas nozzle when the temperature of the molten metal was higher than the range of 380°C to 390°C. The temperature of the molten metal was almost the same as the steel sheet temperature, so it was substituted with the steel sheet temperature. In this manner, hot-dip plated steel sheets Nos. 1 to 36 shown in Tables 1A and 1B were produced.
[0069] The optimum temperature range for the molten metal when spraying liquid nitrogen was estimated using "Thermo-Calc" (Thermo-Calc is a registered trademark of Thermo-Calc Software). In the thermodynamic equilibrium calculation using "Thermo-Calc", a general database was used, and the phase to be excluded from the calculation was Mg2Zn, which is difficult to observe in the actual plating structure. 11After specifying the Al phase and the Si phase, the formation start temperature of Mg2Si in the target composition was calculated. The actual formation temperature of Mg2Si is about 10 to 40°C lower than the above calculated temperature due to the influence of supercooling and the amount of formation, so this temperature range was set as the optimal temperature range of the molten metal when spraying liquid nitrogen. For example, the formation start temperature of Mg2Si calculated in a coating composition of Al: 11%, Mg: 3%, and Si: 0.2% was about 400°C, so it was decided to spray liquid nitrogen when the temperature of the molten metal was in the range of 360°C to 390°C, preferably in the range of 380°C to 390°C. In the same manner, the optimal temperature range of the molten metal when spraying liquid nitrogen was estimated in the coating composition shown in Table 1A. In the column of the steel sheet temperature when spraying liquid nitrogen in Table 1A, the underlined temperatures mean that they are outside the estimated optimal temperature range.
[0070] In addition, a hot-dip galvanized steel sheet was produced in the same manner as above, except that liquid nitrogen was not sprayed. A square pattern with a side length of 50 mm was printed on the surface of the hot-dip galvanized layer of this steel sheet by an inkjet method. In this manner, hot-dip galvanized steel sheet No. 37 was produced.
[0071] In addition, a hot-dip galvanized steel sheet was produced in the same manner as above, except that the liquid nitrogen was not sprayed. Then, the surface of the hot-dip galvanized layer was ground to form a square pattern with a side length of 50 mm. In this manner, hot-dip galvanized steel sheet No. 38 was produced.
[0072] For the obtained hot-dip plated steel sheet, the number density of Mg2Si per area was measured in the patterned part and the non-patterned part of the hot-dip plated layer on the side opposite to the side sprayed with liquid nitrogen. First, the boundary between the patterned part and the non-patterned part was identified by observing the surface of the hot-dip plated layer with the naked eye. In cases where it was difficult to distinguish the boundary, the area sprayed with liquid nitrogen was considered to be the patterned part.
[0073] The method for measuring the number density of Mg2Si was as follows. The hot-dip galvanized layer was gradually ground from the surface, and the newly emerged ground surface was observed under an electron microscope, and the number density of Mg2Si on the ground surface was measured. This operation was repeated until the steel sheet surface was exposed. The amount of grinding per time was set to a depth of 1 μm. The number density of Mg2Si on each ground surface was compared, and the ground surface with the highest number density of Mg2Si was determined as the interface between the hot-dip galvanized layer and the steel sheet. The number density of Mg2Si on the interface was determined as the number density of Mg2Si in the patterned part or non-patterned part. The number density was measured for each patterned part and non-patterned part. The observation area for measuring the number density was 0.2 mm 2 The number density was measured for five regions in each of the patterned and non-patterned parts, and the average values were taken as the number density of each of the patterned and non-patterned parts. The ratio of the number density of Mg2Si in the patterned part to the number density of Mg2Si in the non-patterned part was then calculated.
[0074] [Distinguishing property] The square patterned test panels were visually evaluated according to the following criteria for both the initial state immediately after production and the aged state after six months of outdoor exposure. For both the initial state and the aged state, a rating of ⊚ to △ was considered to be acceptable.
[0075] ◎: The square pattern can be seen from 8m away. ○: The square pattern cannot be seen from 8 m away, but it is highly visible from 4 m away. △: The square pattern cannot be seen from 4m away, but is highly visible from 1m away. ×: The square pattern cannot be seen from 1m away.
[0076] [Corrosion resistance] The test plates were cut to 150 x 70 mm and subjected to 30 cycles of accelerated corrosion testing (CCT) in accordance with JASO-M609. The occurrence of rust was then investigated and evaluated according to the following criteria. A score of ⊚ to △ was deemed to be acceptable. ⊚: No rust was observed, and both the square pattern and other areas maintained a beautiful design and appearance. ◯: No rust was observed, but very slight changes in the design and appearance were observed in the square pattern and other areas. Δ: The design appearance is slightly impaired, but the square pattern and other areas are visually distinguishable. ×: The appearance quality of the square pattern and the other areas is significantly deteriorated and cannot be distinguished by visual inspection.
[0077] As shown in Tables 1A and 1B, the hot-dip galvanized steel sheets of the present invention, No. 1 to No. 29, were excellent in both identifiability and corrosion resistance. FIG. 1 shows the results of observation of the patterned part of No. 1 by a scanning electron microscope, and FIG. 2 shows the results of observation of the non-patterned part of No. 1 by a scanning electron microscope. FIG. 1 and FIG. 2 are the results of observation at the same magnification. In FIG. 1 and FIG. 2, the black particles are Mg2Si. In the patterned part, there were many Mg2Si particles of 10 μm or less, and in the non-patterned part, there were sparse Mg2Si particles of 10 μm or more, and the number of Mg2Si particles in the patterned part was more than twice that of the non-patterned part. As a result, the area in FIG. 1 had a glossy appearance, and the area in FIG. 2 had a matte appearance. Thus, it can be seen that the patterned part and the non-patterned part have different appearances and can be distinguished.
[0078] In No. 30, the temperature of the molten metal when the liquid nitrogen was sprayed was not appropriate, so the pattern was not formed and as a result, the square pattern did not appear. Nos. 31 to 34 did not satisfy the discrimination ability or corrosion resistance because the chemical composition of the plating layer was outside the range of the present invention. In No. 35, since the plating layer did not contain Si, Mg2Si was not found in the plating layer. Therefore, the number density of Mg2Si in Table 1B is recorded as "0". Thus, since Mg2Si was not formed, the pattern part was not formed, and as a result, the square pattern was not formed. In No. 36, the plating layer contained excessive Si, which increased the number density of Mg2Si in the non-patterned area. As a result, the number density ratio was less than 2.0, and the patterned area could not be visually confirmed. As a result, the square pattern did not appear.
[0079] In addition, for No. 37, which had a square pattern printed using the inkjet method, the pattern faded after six months of outdoor exposure, and the design quality deteriorated. Furthermore, in the case of No. 38 in which a square pattern was formed by grinding, the thickness of the plating layer in the ground areas was reduced, and the corrosion resistance in the ground areas was reduced. The hot-dip coating layers of Nos. 1 to 2, 4 to 30, and 32 to 38 contained an [Al phase] and an [Al / Zn / MgZn2 ternary eutectic structure].
[0080] FIG. 3 shows the surface of a hot-dip galvanized steel sheet having a character string (alphabet) formed by a pattern portion in the hot-dip galvanized layer. According to the present invention, it becomes possible to intentionally display characters or marks on the surface of a hot-dip galvanized steel sheet.
[0081] [Table 1A]
[0082] [Table 1B]
Claims
1. A steel sheet and a hot-dip plating layer formed on a surface of the steel sheet, The hot-dip plating layer contains, in average composition, Al: 4 to 22 mass%, Mg: 1.0 to 10 mass%, Si: 0.01 to 2.0 mass%, and the balance contains Zn and impurities, The hot-dip coating layer has an intermetallic compound, Mg 2 Contains Si, The hot-dip plating layer has a pattern portion and a non-pattern portion arranged to have a predetermined shape, Mg per area in the pattern portion 2 The number density of Si is Mg per area in the non-patterned portion. 2 The number density is 2.0 times or more the number density of Si, the number density of Mg 2 Si per area in the pattern portion is 100 particles / mm 2 or more; The hot-dip galvanized steel sheet, characterized in that the pattern portion is intentionally formed.
2. Mg per area in the non-patterned portion 2 The number density of Si is 1000 pieces / mm 2 2. The hot-dip galvanized steel sheet according to claim 1, wherein:
3. The hot-dip plated steel sheet according to claim 1 or 2, characterized in that the hot-dip plated layer further contains, in an average composition, one or more of Ni, Ti, Zr, Sr, Fe, Sb, Pb, Sn, Ca, Co, Mn, P, B, Bi, Cr, Sc, Y, REM, Hf, and C in a total amount of 0.0001 to 2 mass%.
4. The hot-dip galvanized steel sheet according to any one of claims 1 to 3, characterized in that the pattern portion is arranged so as to have a shape that is one or a combination of two or more of a straight line portion, a curved line portion, a dot portion, a figure, a number, a symbol, a design, or a letter.
5. The coating weight of the hot-dip coating layer on both sides of the steel sheet is 30 to 600 g / m 2 The hot-dip plated steel sheet according to any one of claims 1 to 4,
Citation Information
Patent Citations
JP1975043234A
Atsudenseijikino seizohoho
JP1976041899A
Hot-dip galvanized steel sheet with excellent formability
JP3600804B2
High-corrosion-resistance hot-dip galvanized steel plate having highly uniform appearance and manufacturing method therefor
WO2013002358A1
Zinc alloy plated steel material having excellent corrosion resistance after being processed and method for manufacturing same
WO2019132336A1
